Decadal decrease of Antarctic sea ice extent inferred from whaling records revisited on the basis of historical and modern sea ice records - Ackley, Stephen; Wadhams, Peter; Comiso, Josefino C; Worby, Anthony P (Polar Research, 2003)
In previous work, whaling catch positions were used as a proxy record for the position of the Antarctic sea ice edge and mean sea ice extent greater than the present one spanning 2.8° latitude was postulated to have occurred in the pre-1950s period, compared to extents observed since 1973 from microwave satellite imagery. The previous conclusion of an extended northern latitude for ice extent in the earlier epoch applied only to the January (mid-summer) period. For this summer period, however, there are also possible differences between ship and satellite-derived measurements. Our work showed a consistent summer offset (November– December), with the ship-observed ice edge 1 - 1.5° north of the satellitederived ice edge. We further reexamine the use of whale catch as an ice edge proxy where agreement was claimed between the satellite ice edge (1973–1987) and the ship whale catch positions. This examination shows that, while there may be a linear correlation between ice edge position and whale catch data, the slope of the line deviates from unity and the ice edge is also further north in the whale catch data than in the satellite data for most latitudes. We compare the historical (direct) record and modern satellite maps of ice edge position accounting for these differences in ship and satellite observations. This comparison shows that only regional perturbations took place earlier, without significant deviations in the mean ice extents, from the pre-1950s to the post-1970s. This conclusion contradicts that previously stated from the analysis of whale catch data that indicated Antarctic sea ice extent changes were circumpolar rather than regional in nature between the two periods.
Keywords: Sørishavet; Weddellhavet; endringer; havis; historisk; hvalfangere; hvalfangst; iskant; observasjoner; satellite bilder; sjøis

In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2003)
Keywords: Antarktis; Norge; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

Bønder i Antarktis : hvalfangst og landbruk 1925-1940 - Lalla, Robert (Institutt for økonomi og ressursforvaltning, Norges landbrukshøgskole, 2003)
Keywords: Norge; Sørishavet; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie